The evolution of the press image in the Iraqi press (An analytical study of the pictures of the first page of Al-Sabah newspaper for the year) - Abedullah, Saad Salman (ALBAHITH ALALAMI, 2019)
This research sheds light on the development that has occurred on the use of press pictures in the Iraqi press by analyzing the form and content of the images used in (Al-Sabaah) newspaper for the 2012 model. The researcher's interest in this topic for what represented by the press picture of a way to highlight and attract the reader's attention to the substance journalist who represents the goals behind the newspaper publishing.This research is divided into three sections. The first one dealt with the methodological framework of the research, and the second part addressed the aspect of press pictures and its history and technological development, while the third section devoted to the study of the development of the form and content of the press is in the Iraqi press.The results of the search to confirm the following:• Al-Sabah newspaper, through its transformation from the traditional mode to the electronic production mode, used modern techniques to produce the press picture to be suitable for publishing through electronic means in a very fast, flexible and accurate and using many of the software provided by the technological development in this production field.• Al-Sabah newspaper was interested in highlighting advertising pictures in the first place, and second place came in the news function of the press picture by reviewing a group of important events regionally and internationally.• During the research period, Al-Sabaah newspaper focused more on its use of press pictures in the local field than in the regional, Arab and international fields. Despite the use of this field, we see that the source of the local press picture was mostly from Reuters, followed by the French Press Agency.• Al-Sabaah used its best available image to dominate the first page in size and position, at the top of the page on the left and on an area spanning two columns to more than four columns.• Al-Sabaah newspaper has written the commentary on the picture in the present tense form to reinforce its status, and the explanation in the description was limited to the event shown in the press picture.